TEACHING VOCABULARY IN CONTEXT AND ITS PRINCIPLES (SCIENCE TIME JOURNAL, 2026)
The significance of vocabulary, its categories, the criteria for choosing words, as well as vocabulary size, depth, and teaching principles were not clearly understood. This article aims to address this challenge. To accomplish these objectives, a systematic review of previously conducted studies and relevant theories was carried out. The findings indicated that vocabulary plays a significant role as a foundation for communication, a representation of social reality, a source of emotional expression, and a predictor of academic performance.